Preoperative Factors Predicting Survival After Secondary Cytoreduction for Recurrent Ovarian Cancer. Issue 5 (1st July 2011) - Frederick, Peter J.; Ramirez, Pedro T.; McQuinn, Lacey; Milam, Michael R.; Weber, Diane M.; Coleman, Robert L.; Gershenson, David M.; Landen, Charles N.
Abstract : Objective: We evaluated preoperative data that may predict benefit from secondary cytoreductive surgery (CRS) to assist in selecting therapy for patients with platinum-sensitive recurrent epithelial ovarian cancer. Materials and Methods: Inclusion criteria included recurrent epithelial or primary peritoneal carcinoma with an initial disease-free interval more than 6 months after chemotherapy, evidence of disease on imaging studies and indication for surgery being to debulk residual disease. Preoperative CA125 values, computed tomographic findings, and time to progression were evaluated as predictors of survival in addition to postoperative information and perioperative morbidity. Results: Sixty-two patients met the inclusion criteria. In the 35.5% of patients debulked to no visible disease, median survival was significantly longer than in those with less than 1 cm of visible residual disease (5.95 vs 2.73 years, P = 0.004), but debulking to less than 1 cm visible disease was not better than those with less than 1 cm residual disease (2.02 years). Mean preoperative CA125 levels were significantly lower in the patients who could be debulked to no visible residual disease compared to less than 1 cm or more than 1 cm residual disease (69.1 vs 290.7 vs 1978.4, P = 0.001). Generation of a receiver operating characteristic curve determined that a CA125 cutoff of 250 U/mL best predicted successful cytoreduction to no visible disease. Conclusions: Only patients cytoreduced to no visible disease achieved a survival advantage, and the only preoperative factor that could predict surgical success regarding prolonging survival was a CA125 less than 250 U/mL. These data can guide physicians and patients in deciding whether or not to undergo secondary cytoreduction for first recurrence of ovarian cancer.